P-C9 Differentiation of MonoMac-1 cell line induced by M-CSF and glucocorticoid pathways. (March 2017) - Rappaport, Jay; Fischer, Tracy; Lehmicke, Gabrielle
Abstract : Monocytes and macrophages have an important role in HIV-1 infection, capable of serving as reservoirs of HIV infection, but also for their potential role in modulating adaptive immunity, thereby having the potential to contribute to the pathogenesis of AIDS. Virus-host interactions appear to result in altered immune polarization and immune suppression through the process of altered macrophage immune polarization. CD163+/CD16+ monocytes are considered a more mature monocyte, and their frequency has been correlated directly with viral load and inversely with CD4+ T cell count. These cells be a precursor to alternatively activated or Type 2 macrophages, which may dampen immune responses in tissues in HIV infection. The CD163+/CD16+ monocyte subset has been reported to be preferentially infected by HIV and furthermore, carries HIV DNA in HIV infected patients. To develop strategies to reduce or target this subset therapeutically, we performed studies to establish as cell culture model system to test compounds of interest. In our studies presented here, we investigated the effects of PMA, LPS, DEX and M-CSF on the expression of CD163 and CD16 as determined by flow cytometry. Using a stepwise approach, using MONO-MAC-1 cells treated with PMA and PMA + LPS for 3 days followed by DEX+MCSF for 4 days, we were able to increase expression of CD163 and CD16. These affects appear to be due to the action of Dexamethasone and M-CSF on the cognate glucocorticoid and cFMS receptors respectively as RU486 and PLX3397 exhibited inhibitory effects. Our results may provide insights regarding the role of M-CSF and glucocorticoids on myeloid differentiation and furthermore, may emphasize the potential of targeting these pathways for therapeutic intervention in disease states such as HIV infection, cardiovascular disease, and metabolic syndrome, where this monocyte subset is increase. The culture conditions we established useful for screening other compounds that have therapeutic potential in affecting monocyte macrophage differentiation.